Modiﬁcation of the fermentation process and papain enzymes in the manufacture of virgin coconut oil using optimization of response surface methodology, central composite design - Jakfar, Jakfar; Husin, Husni; Pontas, Komala; Mamat, Rizalman; Salleh, Mohd Rosdi; Zulrika, Mirna; Ahmadi, Ahmadi (MDPI, 2023)
This research focuses on optimizing fermentation modification and papain enzymes. In manufacturing virgin coconut oil using the response surface methodology (RSM), the experiment was carried out based on the Central Composite Design (CCD). Coconut oil yield, as a function of crude papain enzyme (CPE) mass (0–1 g) and fermentation time (12–60 h), was observed for 13 runs. The yield of virgin coconut oil with natural fermentation without the addition of crude enzyme papain is 19%, and with the addition of 1 g of the enzyme, it can reach a maximum of 27.7%. Optimal conditions were obtained at a mass of crude papain enzyme 993.5 mg, fermentation time 60 h respectively, yields: Banda Aceh virgin coconut oil (BAVCO) 28.4%, Pidie Jaya virgin coconut oil (PJVCO) 25.6%, and Bireuen virgin coconut oil (BVCO) 24.7%, quality of virgin coconut oil (VCO): water content (WC) 0.047%, free fatty acid (FFA) 0.01%, and peroxide (PN) 0.024% from each of the total mass of 300 g grated coconut, VCO modified by fermentation with the addition of CPE increased the yield. The quality of VCO in terms of WC, FFA, and PN meets the VCO quality standard. The optimization for desirability was 0.998, and the product had a transparent color, a distinct aroma, and did not have a putrid aroma.